(3GdhSjW aj GdCeKGds - (3Ydj Hf CMeO Hf eMeO Hf Ydj Hf neoqJhjI, CHh GdMSf GdhGMOj GdfjSGHhQj , J (B468 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi cd MGd hHYO aEfg deG cGf GdeLdS GdSGMi dGjfi GdfLjHi GdNWjQi GOGe Gddg Sehg s
(3BNQgG (B:s
(3CNQg eHJhQ hjfJgi CKfGA GdHGH GdJGSY hGdYTQjf hgh BNQ CHhGH GdcJGH hBNQ GdehLhO efg (B: (3hdh Cfge bJdhG eGdckG dcfJ dge MjI GUOI aSeYJ Ce SeGc Pdc abGdJ (B: (3jG eGdc bHM Gddg s
(3HgG fXGe GdJYbjHIs
(3ai CKfGA GdfSNI HJQ cHjQ JQc dg YOI cQGQjS HjVGA hgPG GdHJQ jHOC CKfGA GdHGH GdSGOS GdeJVef MQa GdMGA GdegdeI hjfJgi YfO Chd GdHGH GdQGHY YTQ eeG Chdg MQa GdUGO GdegedIs
(3LYdg ai JSYI hYTQjf HGHkG Ydi MQha GdeYLes
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs